SERANGAN KUMBANG AMBROSIA PLATYPUS TREPANATUS PADA DOLOK RAMIN - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1988)
The infestations of ambrosia beetle Platypus trepanatus Chap. (Coleoptera:  Platypodidae)    on  felled  ramin trees (Gonystylus bancanus  Kurz.)  were studied  in a logging area of  West Kalimantan. Three felled ramin trees, d.b.h,  approximately 25  cm,  were prepared  for  the  beetle  infestations   on  their  felling  sites  for 20 days.  Six sections of each  trunk, each of  0.5 m length, which  were consecutively arranged at intervals 2.0 m started  from  the basal, were observed.  Number of  the  beetle  tunnels  on each trunk  section  were counted, and diameter,  area of surface, and volume  of the trunk  sections, were  measured.More  tunnels   were  found   on  the  larger diameter  of  trunk  sections.  However,  analyses  of  the  data showed  no  discernible  trends  for  the  intensity   of  the  beetle  attacks   in  different   trunk  sections  and  that  the size  as well.  Those,  the increasing number  of  the  tunnels  of  the  beetle   is in lines   with  the increase  of  the  host  sizes.